Pengaruh Budaya Organisasi, Kecerdasan Emosional dan Lingkungan Kerja Terhadap Organizational Citizenship Behavior - Berlianto, Wildan Pramestia Nur; Slamet, Afi Rachmat; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study purpose to analyze the influence of organizational culture, emotional intelligence, and work environment on organizational citizenship behavior (OCB) among teachers at Madrasah Ibtidaiyah (MI) in Malang City. This research employs an explanatory research method with a quantitative approach. The sample consists of 60 teachers selected using a saturated sampling technique from four MI schools in the Lowokwaru District. The data were analyzed using multiple linear regression to examine the relationship between the independent variables (organizational culture, emotional intelligence, and work environment) and the dependent variable (OCB). The results show that organizational culture, emotional intelligence, and work environment simultaneously have a significant influence on OCB. Partially, each of the three independent variables also has a positive effect on OCB. The Adjusted R² value of 57.3% indicates that the model used is able to explain a majority of the variation in OCB. These findings emphasize the importance of improving organizational culture, emotional intelligence, and the work environment in fostering organizational citizenship behavior within the educational context. Keywords: Organizational Culture, Emotional Intelligence, Work Environment, Organizational Citizenship Behavior